2021
DOI: 10.1016/j.mnl.2020.08.001
|View full text |Cite|
|
Sign up to set email alerts
|

The Professional Quality of Life and Work Engagement of Nurse Leaders

Abstract: Even before the current pandemic, the nurse leader (NL) role was demanding of time, energy, and resources. These demands often cause stress, fatigue, and burnout. The focused-on outcome metrics, increased regulations, and economic downturn are challenges that NLs have continued to face. This study, undertaken before the pandemic, provides understanding of the professional quality of life and work engagement among NLs. Findings revealed that experienced NLs with doctorates have higher levels of compassion satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 13 publications
5
37
0
2
Order By: Relevance
“…The results regarding ProQOL showed a moderate level of CS with a mean ± SD was 38.15± 7.392. This result consists with Adolfo (2021) and Remegio et al (2021) which they found a moderate level of CS. This can be due to feeling job satisfaction and empathy among nurses working in critical care units, but stress at work and the difficulties they face can affect their job satisfaction (Dodek et al, 2016) or can interfere with feelings of joy, empowerment, energy, and exhilaration (Huang et al, 2020), as caregivers continue to see the positive impact with their patient's improved health conditions (Yılmaz & Üstün, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…The results regarding ProQOL showed a moderate level of CS with a mean ± SD was 38.15± 7.392. This result consists with Adolfo (2021) and Remegio et al (2021) which they found a moderate level of CS. This can be due to feeling job satisfaction and empathy among nurses working in critical care units, but stress at work and the difficulties they face can affect their job satisfaction (Dodek et al, 2016) or can interfere with feelings of joy, empowerment, energy, and exhilaration (Huang et al, 2020), as caregivers continue to see the positive impact with their patient's improved health conditions (Yılmaz & Üstün, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…At the end of the study, it was determined that the nurses had a low level of SMA and a moderate level of WE. In Gou et al, 37 and Remegio et al, 38 studies, it was revealed that nurses' WE levels were above the average. Unlike the results obtained from this study, while SMA levels were moderate in studies by Javed et al, 12 Majid et al, 5 and Balcı et al, 49 they were high in Korkmaz et al 16 In the present study, the low level of social media use of nurses whose work engagement was at a moderate level, which probably stems from the fact that, as stated in the literature, nurses engaged in their work dedicated more of their time to their profession and patients 21,27 .…”
Section: Discussionmentioning
confidence: 92%
“…Remegio et al. likewise had a predominance of female responses (88.9 %), and most responders were nurse leaders, who had poor QOL [50] . Feminization of medicine can be one explanation [51] .…”
Section: Discussionmentioning
confidence: 94%